Hybrid‐RRAM toward Next Generation of Nonvolatile Memory: Coupling of Oxygen Vacancies and Metal Ions. (23rd November 2018) - Sassine, Gilbert; Nail, Cécile; Blaise, Philippe; Sklenard, Benoit; Bernard, Mathieu; Gassilloud, Rémy; Marty, Aurélie; Veillerot, Marc; Vallée, Christophe; Nowak, Etienne; Molas, Gabriel
Abstract: Here, the impact of copper and oxygen vacancy balance in filament composition as a key factor for oxide‐based conductive bridge random access memories (hybrid resistive random access memories (HRRAMs)) performances is investigated. To this aim, several RRAM technologies are studied using various resistive layers and top electrodes. Material analyses allow to highlight the hybrid aspect of HRRAM conductive filament. Density functional theory simulations are used to extract microscopic features and highlight differences from a material point of view. Integrated RRAM technology performances such as window margin, endurance, and retention are then measured to analyze copper and oxygen vacancy influence on device characteristics. A new RRAM classification correlating filament composition and memory performances is proposed. Abstract : The impact of copper and oxygen vacancy balance in filament composition in hybrid resistive random access memories (HRRAMs) is investigated. Material analyses allow the hybrid aspect of HRRAM conductive filament to be highlighted. Density functional theory simulations are used to extract microscopic features. Integrated RRAM technology performances (window margin, endurance, and retention) are measured to analyze copper and oxygen vacancy influence on device characteristics.